Impact of Socioeconomic Inequalities on Dental Caries Status in Sardinian Children - Dettori, Marco; Arghittu, Antonella; Cappai, Andrea; Castiglia, Paolo; Campus, Guglielmo (Children (Basel), 2024)
Background: The association between oral health of schoolchildren living in the North Sardinia area and socioeconomic deprivation was assessed to evaluate a potential spatial correlation. Methods: A total of 10,947 subjects were examined (5281 aged 3–5-years, and 5666 aged 6–11-years). The WHO dmft index score was calculated following clinical examination by calibrated examiners. The Sardinian Deprivation Index (IDMS) of the children’s municipalities was also considered. Descriptive, bivariate and multinomial data analysis was conducted to assess the association between clinical data and socioeconomic deprivation. The presence of systematic spatial variation regarding caries experience (dmft) and deprivation status was investigated using a spatial autoregressive analysis. Results: Caries figures were statistically different in the two age groups (dmf > 0, 13.79% in the younger group vs. dmf > 0, 34.20% in the older one, p < 0.01). In a multinomial logistic regression model for caries experience, all the covariates were statistically significantly associated (p < 0.01) in comparison with the base outcome “caries-free”. Linear regression analysis showed a dependence of dmft on IDMS (p < 0.01). Based on this equation, the dmft of the 39 municipalities that did not participate in the survey was estimated. IDMS was statistically significantly associated (p < 0.01) with caries prevalence in the spatial regression model. Conclusions: The deprivation index significantly increased the risk of caries for all categories of caries experience and prevalence compared to caries-free. The relationship between IDMS and caries data was also confirmed by spatial analysis.